Umbilical arterial profiles as predictors of severity of hypoxic ischemic encephalopathy after perinatal asphyxia - Jehangir Allam Bhat; Sajad Ahmad Sheikh; Roshan Ara (Paediatrica Indonesiana, 2020)
Background: Perinatal hypoxic-ischemic encephalopathy (HIE) remains a major cause of neurodevelopmental impairment. Umbilical cord blood analysis provides an objective assessment of newborn metabolic status. Accordingly, it is recommended that physicians attempt to obtain venous and arterial samples when there is high risk of neonatal compromise. Objective To compare the predictive value of umbilical arterial blood pH, lactate and base deficit for subsequent development of severity of hypoxic ischemic encephalopathy (HIE) after perinatal asphyxia and comparison of these parameters to determine which one is superior in predicting severity. Methods Umbilical cord arterial blood of newborns with perinatal asphyxia was tested for pH, lactate, and base deficit estimation. These newborns were evaluated in level III NICU and divided into two groups. Group 1 had no or signs and symptoms of HIE I and group 2 had signs and symptoms of HIE II/III. Values of pH, lactate, and base deficit were tabulated and analyzed by receiver-operating characteristic curves. Optimal cut-off values were estimated based on the maximal Youden index. Results Mean pH was significantly lower in group 2 than in group 1, while lactate and base deficit were significantly higher in group 2 than in group 1. Cut-off points for determining severity of HIE were pH <7.13, lactate >6.89 mg/dL, and base deficit >7 mEq/L. Sensitivity and specificity for these cut-off points were 100% and 91.49% for pH, 100% and 85.11% for lactate, and 82.4% and 91.76% for base deficit, respectively. Predictive abilities of all three parameters were similar in determination of HIE severity. Conclusion Umbilical arterial pH, lactate, and base deficit have excellent accuracy to predict the severity of HIE. All three parameters have similarly good predictive ability.